Exploration of How Geometry is Linked to Learners Daily Life Actives Using the Akan Culture - Atta, Seth Amoako; Bonyah, Ebenezer; Boateng, Francis Ohene; Atta, & Solomon Ohene Amoako (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The study examined how Akan culture affects senior high school geometry instruction. The Akan people live in Ashanti, the study area. The study targeted experienced mathematics teachers and Akan traditional art experts. Purposive and snowball sampling were used to recruit Ten participants, including seven experienced mathematics teachers and three craftsmen. Participants were interviewed using a semi-structured interview guide to gather detailed data. Data was thematically analysed. The analysis showed that there are a lot of interconnections between the Akan culture and school geometry in the area of Akan Games, Akan Architecture, Akan art, Akan vocation and Akan traditions. Therefore, incorporating Akan culture into geometry instruction helps students grasp the concepts and apply them to solve real-world problems. The authors concluded that the Akan culture can be applied to the teaching of geometry to enhance student active participation and promote conceptual understanding.